Africa and the Deep Seabed Regime: Politics and International Law of the Common Heritage of Mankind - Egede, Edwin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book seeks to fill a gap in the existing literature by examining the role of African States in the development and establishment of the regime of the deep seabed beyond national jurisdiction (the Area) and the concept of the Common Heritage of Mankind.
Introduction -- African States and the Evolution of the Regime of the Area and the Common Heritage of Mankind -- African States and Delimitation of the Common Heritage of Mankind Area -- The Legal Status of the Area: Common Heritage of Mankind and African States -- Africa and Part XI of Law of the Sea Convention (LOSC) 1982 Provisions, as Amended by the 1994 Implementation Agreement -- African States and the Institutions of the Common Heritage of Mankind Regime in the Area -- African States: The System of Mining of the Common Heritage of Mankind Resources in the Area -- Participation of African States in Deep Seabed Mining of the Common Heritage of Mankind Resources in the Area: Problems and Prospects -- General Conclusion.
Keywords: Law; Law; Law of the Sea, Air and Outer Space; Political Science, general